Notes on the systematics of Clossiana angarensis (Erschoff, 1870) (Lepidoptera: Nymphalidae) from Western Siberia - R.V. Yakovlev; A.Е. Kareev (Кавказский энтомологический бюллетень, 2013)
Populations of Clossiana angarensis (Erschoff, 1870) from Altai, Sayan Mountains, the West Siberian Plain and the Central Ural are studied. Lectotypes of Argynnis angarensis alticola Suschkin, 1907 and Brenthis selenis samkoi Sheljuzhko, 1931 are designated. Subspecific status of taxa alticola (Suschkin, 1907) and samkoi (Sheljuzhko, 1931) are updated.